Manual de criação de portfólio digital - Oliveira, Erinaldo Silva (Brasil, 2019)
This handbook is a product of the master dissertation “Creation of a portfolio of extension courses for the Itaituba Campus of the Federal University of the West of Pará". The product is a tool aimed at the construction of a specific educational product, the digital portfolio, which is a means of demonstrating and proving learning and reflections during a given process or investigative period. It is also an educational resource that allows communication in an innovative and differentiated way. The intention is to propose a teaching-learning process in which the student is understood as an active subject, stimulated to construct his own learning and his research or knowledge course in a creative and collective way, learning in an autonomous and participative way. In this way, the objective is to demonstrate a teaching and learning process that allows the student to develop new knowledge, identifying new discoveries in a shared educational process, active, constructive and multiplicity, demonstrating learning and reflections materialized in an educational product built through a scientific and technological method (NASCIMENTO-E-SILVA, 2018). The research identified that the portfolios can be elaborated for the most varied purposes, with which a teaching-learning proposal is presented that aims to direct to the productive use of digital technologies, developing the reflexive practice in a modern method of teaching, with the intention of generate diverse skills, such as the ability to work together, creativity, initiative, decision making and entrepreneurial skills, skills that are extremely necessary in today's technological society and the world of work.